John Erskine z Carnock (1695–1768) — adwokat, profesor Uniwersytetu w Edynburgu, pisarz instytucjonalny - Szymura, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is an attempt to describe John Erskine — a Scottish advocate, the second person to hold the chair of Scottish law at the University of Edinburgh, and an institutional writer. The author of An Institute and Principles largely abandoned the comparative approach of his predecessors in favour of a systematic interpretation of Scottish law enriched with scholarly reflection on its nature, whilst taking into proper account the current state of Scottish case law. Erskine’s works have not only provided a foundation for the education of many generations of Scottish jurists, but having found recognition in the eyes of Scottish jurisprudence, they have secured for themselves the status of a subsidiary source of law, and for their author, a great deal of respectability.
Keywords: Scottish law; mixed jurisdictions; institutional writers; Erskine, John (1695-1768); Principles of the Law of Scotland; An Institute of the Law of Scotland